Upaya Pengembangan dan Pembinaan Bahasa Indonesia Melalui Penerapam Kata Baku dan Tidak Baku di MTS Bahlul Ulum - Jodi Iskandar; Ai Cahyani; Wita Adia Amelia; Yuni Ertinawati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study analyzes efforts to develop and foster the Indonesian language through the use of standard and nonstandard words at MTS Bahlul Ulum. The increasing use of nonstandard words among students, influenced by social media and cross-regional interactions, has led to a decline in the awareness of using standard language in academic contexts. A descriptive qualitative approach was used with teachers and students of Class VII H at MTS Bahlul Ulum during the first semester of the 2025/2026 academic year. Data were collected through observation, interviews, and documentation of Student Worksheet (LKPD) results containing 50 questions on standard and nonstandard words. The findings showed that before the language development program, students had an average score of 62.4 in understanding standard and nonstandard words, with errors in commonly used informal words like vidio (standard: video) and antri (standard: antre). After the program, which included class discussions, conversation simulations, and interactive worksheets, the average score increased to 78.6, with 82% of students scoring above 78. The error rate decreased from 45% to 18%, indicating that interactive and contextual language development is effective. Continuous training and curriculum integration are essential to strengthening the use of standard language in the digital era.